Klasifikasi Kematangan Tanaman Hidroponik Pakcoy Menggunakan Metode SVM - Naura Nazhifah; Ibrohim Huzaimi; Angga Bagus Prawira; Tasya Enjelika Saputri; Mas Aly Afandi; Eka Setia Nugraha; Agung Wicaksono; Petrus Kerowe Goran; Lukman Priyambodo; Hanin Latif Fuadi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2022)
Pakcoy is a type of vegetable plant belonging to the Brassica family. Pakcoy plants can be cultivated using hydroponic techniques, namely plant cultivation techniques without soil media. The advantage of cultivating Pakcoy plants using hydroponic techniques is that it does not require a large area of ​​land, so it is easy to apply in the yard. However, cultivation with hydroponic techniques has drawbacks such as farmers need to make regular observations to determine the harvest readiness of each plant. This causes a lack of effectiveness of farmers in cultivating Pakcoy plants. With the development of Machine Learning technology, a model can classify the maturity of Pakcoy plants based on digital image data. By applying the Support Vector Machine (SVM) Algorithm, the Machine Learning model can learn to classify a digital image of Pakcoy plants with the category "Small" to represent immature Pakcoy plants and "Large" to represent mature Pakcoy plants which results in an accuracy level of above 79%. It can be concluded that Machine Learning can be implemented in Pakcoy cultivation activities to support hydroponic farmers.